REPRESENTATION OF NATIONAL MINORITIES IN LOCAL SELF-GOVERNMENT AUTHORITIES OF UKRAINE ON THE EXAMPLE OF THE TRANSCARPATHIAN REGION - Зерницький, Р. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The representation of national minorities in the local self-government authorities of the Transcarpathian region is considered. It was concluded that national minorities do not have problems with the representation in the local self-government authorities if there are a corresponding political force in the constituency that can protect the interests of these national minorities and a sufficient number of citizens to ensure that this party overcomes the threshold of 5%.